High-Resolution Ultrasonography of Peripheral Nerves: Measurements on 14 Nerve Segments in 56 Healthy Subjects and Reliability Assessments - Boehm, J.; Scheidl, E.; Bereczki, D.; Schelle, T.; Arányi, Z. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Purpose: The aim of this study was to assess different aspects of reliability in high-resolution ultrasonography (HRUS) of the peripheral nerves and to establish reference values for the most frequently examined nerve segments.Materials and Methods: A nerve size parameter, the cross-sectional area (CSA) of the C5, C6 and C7 cervical roots, the median, ulnar, radial, superficial radial, peroneal, tibial, and the sural nerves was measured using HRUS at a total of 14 predefined anatomical sites in two different cohorts of healthy subjects (n = 56), and the inter-rater, intra-rater and inter-equipment reliability of measurements was assessed.Results: The mean CSA of the 14 nerve segments ranged from 2 to 10 mm2. The intra-rater, inter-rater and inter-equipment reliability was high with intraclass correlation coefficients of 0.93, 0.98, and 0.86, respectively. The CSA values showed no consistent correlation with age, height, and body weight, but males had significantly larger values than females for nerve segments on the arm after correcting for age, weight and height in multivariate analysis. CSA values did not differ when two independent cohorts were compared.Conclusion: Peripheral nerve ultrasonography is a reliable and reproducible diagnostic method in the hands of experienced examiners. Normal values for several upper and lower extremity nerves are provided by our study.
Keywords: high-resolution ultrasonography; cross-sectional area; peripheral nerves; normal values; reliability